Attitude of UNIMAS Pre-Clinical Medical Students towards Online Learning and the Challenges Faced by Them - Tin, Moe Nwe; Yien, Mary Tang Ing; Izzah Qashrina, Mahiden; Timothy Imban, Jowel; Aamir Hamzah, Juma’adee; Khin, Than Yee; Marina Kapitonova, Kapitonova; Soe Lwin, Lwin; Latt, Swe Swe (a and v publications, 2022)
Introduction: The entire world is having a crisis on the attitudes and challenges faced by people in the e-learning areas. Online learning or e-learning carries the definition of having the education through an online basis. It is realized that online learning establishes various kinds of conceptions and barriers in achieving academic goals. Purpose: This study aims to assess the attitudes and challenges faced by the UNIMAS pre-clinical medical students concerning their academic achievements based on online medical education using e-learning systems. Methodology: In this study, the attitudes of students regarding the challenges faced by respondents and their experience during e-learning are measured. In the online survey conducted among pre-clinical medical students, the sample population was selected through convenience sampling technique taken from Year 1 and 2 medical students of UNIMAS, the data collected concerning their opinion about the experience during e-learning and the challenges faced by them. The sample data collected were statistically analysed using the T-test and Chi-Square test. Results: The results showed few significant correlations of some attitudes towards online learning and the challenges with regard to various socio-demographic factors. The results suggest that some socio-demographic factors affect the attitudes and challenges faced directly or indirectly. Most of the UNIMAS pre-clinical medical students showed a neutral attitude towards online learning while facing moderate challenges in this matter. There was no significant association between the majority variables of the socio-demographic with the respondents' attitudes except for the internet connectivity. Ethnicity and internet connectivity showed a true relationship with the challenges faced by the respondents during online learning. Conclusion: The study concludes no evidence of significant negativity among the students' attitudes with regard to their demographic background and internet connectivity. Although there were students who had faced difficulties with regard to online learning. The study suggests that online learning should have facilitated approaches in achieving total learning activities of students around the world, preparation of competent technical personnel, funding of facilitation, and collaboration between universities, specifically in developing countries.